Ferroelectric Nanocomposites: Direct Detection of Local Electric Polarization in the Interfacial Region in Ferroelectric Polymer Nanocomposites (Adv. Mater. 21/2019). Issue 21 (21st May 2019) - Peng, Simin; Yang, Xiao; Yang, Yang; Wang, Shaojie; Zhou, Yao; Hu, Jun; Li, Qi; He, Jinliang
Abstract : A modified Kelvin probe force microscopy method with nanoscale spatial resolution is reported by Qi Li, Jinliang He, and co‐workers in article number1807722 for direct detection of the local polarization at the matrix–particle interface in ferroelectric nanocomposites. The electric susceptibility of the interface is quantitatively probed, which is higher than that of polymer matrix. It is anticipated that the method may help with judicious design and engineering of high‐performance ferroelectric polymer nanocomposites.